P25 Predictive value of CT calcium score in risk stratification of coronary revascularization, acute coronary syndrome or death in high-risk patients: a single centre registry experience. (21st September 2022) - Brady, Paul; Harries, Iwan; Hamilton, Mark; Strange, Julian; Biswas, Sinjini; Mariathas, Mark; Pennington, Mark; Aung, Myat; Felekos, Ioannis
Abstract : Objective: Atheroma based assessments provide better prognostic information than ischaemia testing. This retrospective registry aims to determine the utility of calcium score for risk-stratification in a high-risk sub-population. Methods: Consecutive patients presenting with chest pain, who had sequential CT-based coronary calcium scan and clinically indicated invasive coronary angiogram were included. Baseline risk-score strata were related to a composite-outcome of time to coronary revascularization, acute coronary syndrome or death. Results: 51 of 356 patients (mean age 65 SD+/-1.59 years, 25% women) had an invasive angiogram (SYNTAX score 4 [IQR 0–11]), following CT-coronary calcium scan (calcium score 292 [IQR 69–743]). Median follow-up time was 2.3 years (IQR 0.31–4.7). The composite-outcome was observed in 26 patients (event-rate 17.9/100 person-years). End-point distributions differed for calcium and SYNTAX scores (Log-Rank p=0.03 and p<0.001, respectively). Calcium score strata was a significant predictor even after adjustment for SYNTAX score tertiles (adjusted hazard ratio 1.76 [95% CI:1.08–2.85]). While calcium score compared less favourably in discriminating risk (Harrell's C-statistic 0.67 [95% CI:0.56–0.77] versus 0.80 [95% CI:0.71–0.89] for SYNTAX score), calcium scores of zero had good negative-predictive-value (100% [95% CI:87%–100%]), while scores ≥1000 had good positive-predictive-value (88% [95% CI:47%–99%]). Conclusion: In a high-risk population, the presence of any calcium in the coronary tree, i.e., calcium score ≥1, is predictive. Calcium score has predictive value in indicating risk at extreme ends of the spectrum (calcium score of zero and ≥1000). Exact scores ranging from 1–1000 offer limited additional value in terms of risk-stratification.